2015
DOI: 10.5070/p2cjpp7225907
|View full text |Cite
|
Sign up to set email alerts
|

Confidence, Perception, and Politics in California: The Determinants of Attitudes toward Taxes by Level of Government

Abstract: California faced a tremendous fiscal challenge in the wake of the 2008 recession. With high political hurdles to raising taxes, the state and local governments were forced to appeal directly to voters through ballot initiatives. Debates over these ballot initiatives, however, took place against the backdrop of increasingly acrimonious disagreements about taxation at the federal level. Unfortunately, researchers have little idea about how the dynamics of public opinion on tax issues operate across these various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…The second group of variables in Table 1 focus on race-related considerations. Confirming the findings from other studies (Beck & Dye, 1982;Beck et al, 1987Beck et al, , 1990Wallsten & Park, 2015) we find that non-whites are typically more willing than white respondents to express anti-tax attitudes. Specifically, respondents of Latino descent are more likely than others to think they pay a lot more than their fair share in local taxes, both black and Latino respondents are more likely than others think it is very important to lower local taxes, and white respondents are the least likely to express anti-tax attitudes.…”
Section: Race Ethnicity and Racial Resentmentsupporting
confidence: 91%
See 2 more Smart Citations
“…The second group of variables in Table 1 focus on race-related considerations. Confirming the findings from other studies (Beck & Dye, 1982;Beck et al, 1987Beck et al, , 1990Wallsten & Park, 2015) we find that non-whites are typically more willing than white respondents to express anti-tax attitudes. Specifically, respondents of Latino descent are more likely than others to think they pay a lot more than their fair share in local taxes, both black and Latino respondents are more likely than others think it is very important to lower local taxes, and white respondents are the least likely to express anti-tax attitudes.…”
Section: Race Ethnicity and Racial Resentmentsupporting
confidence: 91%
“…Income is positively related to feeling that you are paying more than your fair share in local taxes but negatively related to thinking that it is very important to reduce local taxes. 14 Although the finding for the reduce taxes model is at odds with conventional wisdom, it is in keeping with some findings from the literature (Bartels, 2005;Donahue & Miller, 2016;Wallsten & Park, 2015) and may indicate an "ability to pay" rather than a self-interest effect (Roscoe, 2013).…”
Section: Robustness Checkssupporting
confidence: 53%
See 1 more Smart Citation
“…The assumption that the politics of taxation are one-dimensional is at odds with a growing body of evidence that voters may evaluate any given local tax along multiple dimensions simultaneously. Public opinion research shows that taxes vary substantially in their popularity (Campbell 2009;Williamson 2017), and that taxpayers evaluate taxes based on such considerations as how fair they believe them to be (Kidder and Martin 2012), how unpleasant they find the experience of paying (Williamson 2017), and how confident they are that the government will spend the revenue appropriately (Fairbrother 2017;Wallsten and Park 2015). These dimensions, in turn, may be affected by the qualitative design of the policy.…”
Section: Degrees Of Freedom In Municipal Tax Policymentioning
confidence: 99%
“…Relevant research has demonstrated that green-technology innovation can lower corporate carbon emission levels [ 27 ] and effectively promote carbon-emission responsibilities. Additionally, independent technological innovation can have a remarkable effect on carbon-emission reduction [ 28 ]. Of course, apparent regional differences can be found; independent research and development has impacted carbon-emission reduction in East and West China, but the impact in Central and Northeast China has been insignificant.…”
Section: Literature Review and Hypothesis Proposedmentioning
confidence: 99%